2020
DOI: 10.1055/a-1085-9250
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Retinal Vessel Pulsations with Electrocardiographic Gating

Abstract: Purpose The origin of retinal venous pulsations has been a matter of debate for some time. One classical explanation to the origin of these pulsations has been that the cardiac cycle induces systolic peaks in the intraocular pressure (IOP) which leads to decreases in retinal vein diameters. Recently, theoretical concepts have been published which postulate that IOP changes during the pulse cycle is not the primary driving force for venous pulsation, and hence, predict that the retinal vein diameter is indeed r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The results of the proposed approach show that the estimated Tvc values are in agreement with the results published in the papers, which use the ECG signal as a trigger (the blue part in Fig. 9 ) [ 7 , 12 , 13 ]. Shortly, Chen et al [ 12 ], in 1994, used ECG to trigger fundus camera acquisition in 8 increasing delays after the R-wave.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results of the proposed approach show that the estimated Tvc values are in agreement with the results published in the papers, which use the ECG signal as a trigger (the blue part in Fig. 9 ) [ 7 , 12 , 13 ]. Shortly, Chen et al [ 12 ], in 1994, used ECG to trigger fundus camera acquisition in 8 increasing delays after the R-wave.…”
Section: Discussionsupporting
confidence: 87%
“…They evaluated 12 healthy subjects. Bollinger et al [ 7 ] in 2020 took advantage of a commercially available RVA device (Imedos UG, Jena, Germany) and connected this retinal camera with an ECG device for simultaneous acquisition. The diameter of the vessel was also extracted using the RVA software.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it has been reported that elevated IOP did not induce retinal vein collapse. Moreover, IOP and retinal vein diameters seem to be in phase, which may suggest the IOP is not the major driving force of retinal vein pulsations (Bollinger et al, 2020).…”
Section: What Do We Not Know and Want To Know About Prostaglandin Ana...mentioning
confidence: 99%